1995
DOI: 10.1016/0014-5793(95)01117-w
|View full text |Cite
|
Sign up to set email alerts
|

DNA strand breakage and base modification induced by hydrogen peroxide treatment of human respiratory tract epithelial cells

Abstract: Treatment of human respiratory tract epithelial cellswith H202 led to concentration-dependent DNA strand breakage that was highly-correlated with multiple chemical modifications of all four DNA bases, suggesting that damage is due to hydroxyl radical, OH'. However, the ma|or base damage occurred to adenine. Hence, conclusions made about the occurrence and the extent of oxidative DNA damage on the basis only of changes in 8-hydroxyguanine should be approached with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 28 publications
(53 reference statements)
0
38
0
1
Order By: Relevance
“…The induction of DNA strand breaks by exposure of human cells to H 2 O 2 corresponds to a mechanism of oxidative DNA damage [49] and is well correlated with multiple DNA base lesions [50], so we would expect AA to enhance the formation of these lesions too. Other authors have recently reported an enhancing effect of AA on H 2 O 2 -induced formation of 5-hydroxy-2'-deoxycitidine, a product of hydroxyl radical-induced oxidation of 2'-deoxycytidine [51].…”
Section: Discussionmentioning
confidence: 99%
“…The induction of DNA strand breaks by exposure of human cells to H 2 O 2 corresponds to a mechanism of oxidative DNA damage [49] and is well correlated with multiple DNA base lesions [50], so we would expect AA to enhance the formation of these lesions too. Other authors have recently reported an enhancing effect of AA on H 2 O 2 -induced formation of 5-hydroxy-2'-deoxycitidine, a product of hydroxyl radical-induced oxidation of 2'-deoxycytidine [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, other modifications of guanine or other bases also occur, causing their reduction or ringopening. 68 The consequences of base modifications for mtDNA integrity vary depending on the lesion. For instance, ring fragmentation of bases would block DNA replication.…”
Section: Mtdna As a Target For Ethanol-induced Oxidative Stressmentioning
confidence: 99%
“…Effect of gas phase cigarette smoke on HBE cell viability. Viability tests were conducted using the Alamar blue assay, which measures mitochondrial metabolic activity, as described in [18,22]. Means are the result of three separate experiments.…”
Section: Lllhourlmentioning
confidence: 99%